Pathogenic IgG4 autoantibodies from endemic pemphigus foliaceus recognize a desmoglein-1 conformational epitope. (May 2018) - Evangelista, Flor; Roth, Aleeza J.; Prisayanh, Phillip; Temple, Brenda R.; Li, Ning; Qian, Ye; Culton, Donna A.; Liu, Zhi; Harrison, Oliver J.; Brasch, Julia; Honig, Barry; Shapiro, Lawrence; et al.
Abstract: Fogo Selvagem (FS), the endemic form of pemphigus foliaceus, is mediated by pathogenic IgG4 autoantibodies against the amino-terminal extracellular cadherin domain of the desmosomal cadherin desmoglein 1 (Dsg1). Here we define the detailed epitopes of these pathogenic antibodies. Proteolytic footprinting showed that IgG4 from 95% of FS donor sera (19/20) recognized a 16-residue peptide (A 129 LNSMGQDLERPLELR 144 ) from the EC1 domain of Dsg1 that overlaps the binding site for an adhesive-partner desmosomal cadherin molecule. Mutation of Dsg1 residues M 133 and Q 135 reduced the binding of FS IgG4 autoantibodies to Dsg1 by ∼50%. Molecular modeling identified two nearby EC1 domain residues (Q 82 and V 83 ) likely to contribute to the epitope. Mutation of these residues completely abolished the binding of FS IgG4 to Dsg1. Bead aggregation assays showed that native binding interactions between Dsg1 and desmocollin 1 (Dsc1), which underlie desmosome structure, were abolished by Fab fragments of FS IgG4. These results further define the molecular mechanism by which FS IgG4 autoantibodies interfere with desmosome structure and lead to cell-cell detachment, the hallmark of this disease. Highlights: Autoimmune Fogo Selvagem is mediated by pathogenic IgG4 anti-Dsg1 autoantibodies. Desmogleins (Dsg) and desmocollins (Dsc) TRANS interact to mediate epidermal adhesion. IgG4 anti-Dsg1 autoantibodies inhibit the trans interaction of Dsg1 and DsC1. Pathogenic IgG4 anti-Dsg1 autoantibodies bind an epitope on the RAL site of Dsg1. Pathogenic IgG4 anti-Dsg1 autoantibodies cause cell detachment and blisters.